Determinación de ecuaciones entre variables termodinámicas: relación de expansión, presión y temperatura, en la compresión y licuado del gas natural - Vicente Reyes, Magali Elizabeth (2021)
The main objective of this thesis was: Determining the equations between the expansion ratio with pressure and the temperature in the processes of compression and natural gas liquefied. Is investigation has quantitative. The population of study the multiple simulations that can come true in compression and liquefied of natural gas and the type of sampling is not represent it probabilistic, having in account the following opinion of inclusión: Thirty simulations (30) in the compression of natural gas and thirty (30) simulations in the liquefied of natural gas, of which the size results from the similar sample to sixty. The data of the density of the natural gas compressed and liquefied, they gathered themselves of the simulations of the equation of Peng Robinson, getting oneself use of the program Aspen HYSYS V11.0. The obtained results, they show that there is direct relationship between the expansion ratio and the pressure, being this relation a polynomial equation of fourth degree, that is: ????=6×10?8??4?5×10?5??3+0.0103??2+0.7164??+1.9038. The obtained results, also show that there is direct relationship between the expansion ratio and the temperature, which is a linear equation, is it is: ????=?1.6896??+332.97. In conclusion, when having found these equations, he tries on every one of the specific hypotheses and the general hypothesis.